ANALISIS PERMINTAAN BERAS ORGANIK DI KABUPATEN BOYOLALI - Pratiwi Rahayuningsih; Kusriani Prasetyowati; S. SUSWADI; M. MAHANANTO (JURNAL ILMIAH AGRINECA, 2016)
This study aims to determine the factors that influence the demand for organic rice in Boyolali and know the elasticity of demand for organic rice in Boyolali. The basic method of research is descriptive. The research location Boyolali because it is one of organic rice cultivation centers that have high productivity as well as the potential to be developed into a center of organic agriculture products. The results showed the variable price of organic rice and chicken meat prices have a significant effect on the demand for organic rice in Boyolali. Variable non-organic rice, soybean prices, population and per capita income were examined did not significantly affect the demand for organic rice in Boyolali. Organic rice price elasticity is elastic. Cross elasticity of non-organic rice prices marked negative is complements of organic rice. Cross elasticity of tempeh marked negative price which is complements of organic rice. Cross elasticity marked negative price of chicken meat is complements of organic rice. While the income elasticity of 2.400 indicates that organic rice excluding items norm.